Impact of Technological Change on Growth and Agricultural Sector in Gujarat State of India: A Time-Series Data Study - Ashraf, Shah Nawaz; Singh, Ajay K (Asian Development Policy Review, 2021)
This study assessed the growth rate of commercial and food-grain crops due to technological change in Gujarat. Growth rate model was employed to examine the growth rate of area sown, production and yield of crops. Subsequently, impact of technological change, and other inputs on yield of individual crop was estimated using a Cobb-Douglas production function model. Time trend factor was used as a proxy variable to capture the impact of technological change, and other inputs (i.e., area sown, irrigated area, application of fertilizer, agricultural labors, rural literate population and annual actual rainfall) on yield of crops. Growth rate of cropped area, production and yield of cotton, sugarcane, castor, potato, rice, arhar, maize, gram and wheat crops were seemed positive in Gujarat. Yield of cotton, sugarcane, castor, rice, arhar, maize, bajra, gram, wheat, jowar ragi, potato, groundnut, sesamum, rapeseed&mustard and soyabeans crops was positively associated with time trend factors. Furthermore, the regression coefficient of time trend factor with yield of cotton, tobacco, potato, groundnut, sesamum, rapeseed & mustard, rice, arhar, maize, bajra, gram, wheat, jowar and ragi was reported positive and statistically significant. Hence, the estimates shows that yield of aforesaid crops were improved due to application of technological change in agricultural sector in Gujarat. Several practical policy suggestions are given to increase the use of technology in agricultural sector to improve the growth of major food-grain and commercial crops.